(untitled) (Journal of Contemporary Philology, 2024)
Being defined as a concept which entails awareness of one’s own and other people’s emotions and ability to manage those emotions as well as to interpret them in various interpersonal engagements (Goleman, 1998), emotional intelligence (EI) is found to correlate with academic performance, especially with professions with an affective component, including translation and interpreting (Bontempo, 2009; Hubscher-Davidson, 2007). Relying on the results received from the bilateral project “Possibilities for Enhancing Emotional Intelligence as a Generic Competence in Translation and Interpreting Students” (Popovska et al. 2019: 263–276), this paper aims at exploring the possibilities for EI skills enhancement in interpreting students with a view to raising the awareness of the benefits of EI for both teachers and students and adopting new perspectives on career advancement. The results show that the development of EI skills in interpreting students is very important and provides an opportunity for teachers to gain an invaluable insight into the professional development of students and to get inspired to be more creative in improving teaching methodology.